Correlation of FMF criteria scores with severe preeclampsia - prediction of preeclampsia in first trimester - Bhat, Mythri R.; N., Sunanda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: For the prediction of Preeclampsia, a combination of tests and risk factors are superior to single predictors, some multivariable screening algorithms have been developed for predicting PE, one of which is developed by the Fetal Medicine Foundation (FMF) which uses maternal history and a combination of biophysical and biochemical measurements between 11+0 to 13+6 weeks gestation. To apply the FMF algorithm for prediction of preeclampsia in the first trimester, on antenatal women admitted with severe preeclampsia by retrospectively using information from their first trimester visits and to determine the sensitivity in the study subjects. Methods: This is a retrospective study performed using medical records of antenatal women admitted in Cheluvamba Hospital, OBG Department, MMCRI, Mysuru over 12 months period (January 2023 to December 2023) admitted for severe preeclampsia. Results: A total of 7719 deliveries were recorded in Cheluvamba hospital over the 12 months period. 176 antenatal women were diagnosed with Severe Preeclampsia who delivered during this period and were selected for the study. The FMF Algorithm applied using the information obtained from first trimester records (11+0 to 13+6 weeks) correctly predicted: 85% of early onset preterm Severe PE, 93% of late onset preterm Severe PE, 68% of term Severe PE, 81% of all Severe PE Conclusion: The availability of this algorithm as a simple, free to use, online website calculator allows primary care physicians at primary care centers to recognise the potential high-risk pregnancy and to start aspirin prophylaxis, refer her to a tertiary care center for further evaluation and adequate follow up care.